Testing for cointegration in import demand for consumer and non-consumer commodities in the republic of Cameroon - Tambi, N.E. (Informa UK Limited, 1997)
Empirical estimates of the determinants of import demand for consumer and non-consumer commodities in the Republic of Cameroon are derived using cointegration and error-correction modelling. Disaggregation of total merchandise imports into three classes of consumer goods and seven classes of non-consumer goods reveals that imports of consumer goods are more sensitive to import price and income changes than is the case with non-consumer goods. Rising import prices have a depressing effect on trade in consumer goods and appear to encourage demand for domestic substitutes of these goods. Over time, income elasticities of import demand become larger than short-run elasticities, suggesting a greater degree of "openness" of the Cameroon economy.